Evaluation of The Quality of Forest Plant Seedlings on The Nursery at PT Natarang Mining, Tanggamus Regency - Yustika, Vidia; Indriyanto; Asmarahman, Ceng (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2022)
The success of forest rehabilitation is strongly supported by the use of quality plant seedlings. In this study, an evaluation of the quality of the seedlings at the PT Natarang Mining nursery was conducted to determine the quality of the seedlings produced. Data were collected by random sampling with a sampling intensity of 10%, so that the sample used was 1,210 sticks. Observation of research parameters included height, diameter, number of leaves or live crown ratio (LCR), stem condition, health and medium cohesiveness. A total of 60 seedlings were taken for analysis of their wet weight, dry weight and quality index. The results showed that all the seedlings in the nursery were classified as reject seedlings according to SNI Number 8420 of 2018 Concerning Forest Plant Seedlings. Pests and diseases that attack seedlings are naked snails (16.3%) and leaf spot (26.4%). Seedlings that are suitable for planting in the field based on the calculation of the seedling quality index are jackfruit, soursop, nutmeg, and durian with IMBs of 0.113, 0.129, 0.145 and 0.112, respectively. Based on this research, PT Natarang Mining’s nursery needs to improve its nursery technique, especially in handling pests and diseases to improve the quality of the seeds produced. Keywords: seedlings, nursery, seedling quality index